2016
DOI: 10.1021/acs.nanolett.5b02635
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating the Topological Interface by Molecular Adsorbates: Adsorption of Co-Phthalocyanine on Bi2Se3

Abstract: Topological insulators are a promising class of materials for applications in the field of spintronics. New perspectives in this field can arise from interfacing metal-organic molecules with the topological insulator spin-momentum locked surface states, which can be perturbed enhancing or suppressing spintronics-relevant properties such as spin coherence. Here we show results from an angle-resolved photemission spectroscopy (ARPES) and scanning tunnelling microscopy (STM) study of the prototypical cobalt phtha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 45 publications
3
47
2
3
Order By: Relevance
“…Opening the portfolio of inorganic materials for molecular functionalization could create new opportunities currently only hinted at in the literature 76 . Recently, for example, it has been shown that the hybridization of molecules with skyrmions 77 and topological insulators [78][79][80][81] can be used to modify their topologically protected spin texture. In the specific case of topological insulators (Fig.…”
Section: Beyond Inorganic Ferromagnetic Materialsmentioning
confidence: 99%
“…Opening the portfolio of inorganic materials for molecular functionalization could create new opportunities currently only hinted at in the literature 76 . Recently, for example, it has been shown that the hybridization of molecules with skyrmions 77 and topological insulators [78][79][80][81] can be used to modify their topologically protected spin texture. In the specific case of topological insulators (Fig.…”
Section: Beyond Inorganic Ferromagnetic Materialsmentioning
confidence: 99%
“…In real space this topological protection can be followed in the response to defects. The interface states will move around the defects by shifting away from the interface [8][9][10][11] , similar to the simplified picture for the edge state in the quantum hall effect. In momentum space, a topologically protected state has to cross the band gap and this crossing can't be lifted by small perturbations.…”
Section: Simplified View On Topology In Electronic Structurementioning
confidence: 99%
“…Hence, despite the common charging behavior observed for TCNQ on a number of more reactive surfaces, on Bi 2 Se 3 TCNQ adsorbs as a neutral species forming characteristic hydrogen bonded networks, similarly to what observed on other inert surfaces ,. This is different to what has been reported for CoPc/Bi 2 Se 3 or MnPc/Bi 2 Te 3 ,, where a notable charge transfer to the substrate was measured: the adsorption of TCNQ on Bi 2 Se 3 (0001) does not significantly modify the TI surface electronic structure.…”
Section: Resultsmentioning
confidence: 50%
“…Recent calculations indicate that such MOCNs could display an out‐of‐plane magnetic anisotropy on a TI, break the time‐reversal symmetry and induce the opening of an energy gap at the Dirac point of the TSS. The first step towards the fabrication of this type of networks is to investigate the adsorption of a pure layer of electron acceptor molecules and to verify that, on their own, they do not induce a significant modification or disruption of the TSS Dirac cone, as observed for other molecular species on TIs or for similar molecular species on graphene …”
Section: Introductionmentioning
confidence: 99%